Perbandingan Negasi ‘Tidak’ dan ‘Bukan’ Antara Bahasa Indonesia dan Bahasa Mange - Umiatun Sa’diyah (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2016)
This research aims to compare the negators ‘tidak’ and ‘bukan’ in Indonesian and Mange language. The source of data in this research is spoken language collected through observation method, interview, and elicitation. The informants of this research are native speakers of Mange language who live at Air Bulan village, Taliabu Utara subdistrict, Taliabu island, North Maluku Province. The kinds of this research is a fieldwork research with descriptive-qualitative approach. The data was analysed by applying contrastive-analysis method. The finding of this research shows that there are differences between negative constructions in Indonesian and Mange language, namely on the negator position within phrase and sentences, the word order classification, and the negative constituent.